2004
DOI: 10.1080/00480169.2004.36414
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural characteristics of dairy cows with lameness in Taranaki, New Zealand

Abstract: Walking/milking order was a risk factor for conditions causing lameness in dairy cows, and for the effective management of herd lameness problems it is important for farmers to be aware of this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
2
12
1
Order By: Relevance
“…Low social rank was associated with lameness (Galindo and Broom, 2002) and increased standing time (Galindo and Broom, 2000), and thus may increase the risk of lesions. Position in the social hierarchy have been shown to affect the milking position of individual dairy cows (Rathore, 1982;Sauter-Louis et al, 2004). Although we did not monitor milking order, we expect that in our study some primiparous cows were further down the milking order, resulting in increased standing times in the holding area.…”
Section: Lying Behavior and Claw Lesionsmentioning
confidence: 83%
“…Low social rank was associated with lameness (Galindo and Broom, 2002) and increased standing time (Galindo and Broom, 2000), and thus may increase the risk of lesions. Position in the social hierarchy have been shown to affect the milking position of individual dairy cows (Rathore, 1982;Sauter-Louis et al, 2004). Although we did not monitor milking order, we expect that in our study some primiparous cows were further down the milking order, resulting in increased standing times in the holding area.…”
Section: Lying Behavior and Claw Lesionsmentioning
confidence: 83%
“…Many factors have been shown to affect the milking position of individual dairy cows, including position in the social hierarchy (Rathore, 1982;Sauter-Louis et al, 2004); introduction of new animals to the herd (Soffié et al, 1976); stage of lactation (Rathore, 1982;Sauter-Louis et al, 2004); estrus (Scott Mitchell et al, 1996); lameness (Botheras, 2006); milk yield (Rathore, 1982;Berry and McCarthy, 2012); cell count or mastitis (Rathore, 1982;Berry and Mc-Carthy, 2012;Polikarpus et al, 2015); genetics (Berry and McCarthy, 2012); and the presence of disease such as metritis and pneumonia (Polikarpus et al, 2015). The milking order (order in which cows are milked) is also related to the walking order (the order in which they leave the paddock; Sauter-Louis et al, 2004).…”
Section: Short Communicationmentioning
confidence: 99%
“…Correlations between the milking orders of any 2 milkings were very high (on average, r = 0.8-0.9), even for milkings up to 6 mo apart. In 10 New Zealand herds, with an average group size of 183, Sauter-Louis et al (2004) reported Means within a column without a common superscript differ significantly (P < 0.05). Cronbach's α coefficients for milking order >0.9, with increasing walking order stability as the season progressed.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently a series of further studies was undertaken to understand lameness more fully at both cow and herd level Morris 1991, 1992;Tranter et al, , 1993Sauter-Louis et al, 2004). The biggest problem in understanding and managing lameness is that there are no investigational procedures equivalent to the laboratory diagnostic tests used for other diseases.…”
Section: Lameness In Dairy Cattlementioning
confidence: 98%